DOS Kapital: Has antitrust action against Microsoft created value in the computer industry? - Bittlingmayer, G (Journal of Financial Economics, 2000)
Antitrust enforcement that efficiently constrains Microsoft's behavior benefits firms supplying complements to and/or substitutes for Microsoft's operating system and applications software. However, from 1991 through 1997, 29 reports of federal antitrust enforcement action against Microsoft were accompanied by declines in the value of an index of 159 computer industry firms (excluding Microsoft). The mean loss to those firms exceeded $1 billion per event. Eight retreats or setbacks in enforcement were associated with increased computer sector value. Thus, financial markets reveal compelling evidence against the joint hypothesis that (a) Microsoft conduct is anticompetitive and (b) antitrust policy enforcement produces net efficiency gains.